Apparentment as Institution of Electoral Law - Rulka, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
In initial part of the article the author affirms that the multitude of construction of blocking authorizes to put the thesis, that the apparentment deserves on name the institution of electoral law. The first part of the article presents a comparative overview about solutions applying in France, Italy, Switzerland and Belgium, which provide arguments to prove aforementioned thesis about multitude of solutions concerning apparentment. The second part of the paper presents a short history of legal regulation of the issue of joint lists of candidates and much more wider considerations about present solutions. Author put thesis that PiS introducing apparentment to self-governmental election law before elections in 2006 wanted to cause additional mandates. Author points out that electoral failure of this party was caused by the incorrect expectations concerning political rival behavior as well as by the unpredictability of mathematical apparatus of blocking. Article also refers to proposal of introduction examined institution to parliamentarian elections and possible this consequences. Next part of the article discusses conformity describing institution with Polish Constitution. The author comes to conclusion that this institution in construction with self-govermental electoral law violates the principle of generality and the equality of electoral right, additional if blocking would introduce to Sejm’s elections, then this also would be discordant with principle of proportionality. In conclusion author affirms that the most important postulate concerning apparentment is fuel and effective informing the electors about created electoral blocks and consequences of their creation for party being in block.